A Decomposition of the Dual Space of Some Banach Function Spaces. (2012) - Capone Capone, Claudia Claudia; Formica Formica, Maria Rosaria Maria Rosaria
Abstract : We give a decomposition for the dual space of some Banach Function Spaces as the Zygmund space E X P α of the exponential integrable functions, the Marcinkiewicz space L p, ∞, and the Grand Lebesgue Space L p ), θ .